Pengaruh Media Sosial Dan Daya Tarik Wisata Terhadap Keputusan Berkunjung Pada Kebun Jeruk Hijau Manis Desa Pematang Kuing, Kecamatan Sei Suka, Kabupaten Batu Bara - Chairiyah, Chairiyah; Siregar, Dahrul (Training & Research Institute - Jeramba Ilmu Sukses, 2024)
The emergence of so many social media has had an excellent impact, one of which is on the tourism sector. By making it easy to access information on social media related to all travel activities. This research aims to see how much influence social media promotion (X1) and tourist attractions (X2) have on the decision to visit (Y) at the Sweet Green Orange Garden, Pematang Kuing Village, Sei Suka District, Batu Bara Regency. This study uses a quantitative approach. The population in this study was all tourists (period October 2022 - September 2023) of the sweet green orange garden, totaling 7750 visitors. The data was obtained from a Likert scale questionnaire and distributed directly in hardcopy paper containing the questionnaire. The sample for this research comprised 99 samples taken using the Slovin formula, and the sample collection technique used was non-probability sampling in the form of accidental sampling. This research data was analyzed using multiple linear regression analysis. This research shows that the social media promotion variable partially has a positive and significant effect on the decision to visit, and the tourist attraction variable partially has a positive and significant effect on the decision to visit. Meanwhile, the variables of social media promotion and tourist attraction simultaneously have a positive and significant effect on the decision to visit the Sweet Green Orange Garden, Pematang Kuing Village, Sei Suka District, Batu Bara Regency, with an R Square value of 0,414 or 41,4%.